Microfibrillar-associated protein 4 interaction with inflammation and clinical characteristics in neuropsychiatric systemic lupus erythematosus - Wegener, Maria Alexandra Bandehkhoda; Möller, Sören; Olesen, Mads Nikolaj; Madsen, Jonna Skov; Sorensen, Grith Lykke; Voss, Anne; Asgari, Nasrin (Frontiers in Lupus, 2024)
Objectives: Central nervous system (CNS) proteins such as neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) are released into the body fluids following CNS injury. Microfibrillarassociated protein 4 (MFAP4) is an extracellular matrix protein. Recently we reported expression of MFAP4 in CNS and alteration of levels in patients with acute neuroinflammation. We aimed to determine the levels of MFAP4 in a predominantly population-based cohort of systemic lupus erythematosus (SLE) patients, including neuropsychiatric SLE (NPSLE), and to evaluate MFAP4 as a marker of inflammation.In total 208 SLE patients, 44 of those with NPSLE, and 50 age-and sex-matched healthy controls (HC) were recruited. MFAP4 was measured using AlphaLISA immunoassay. NfL, GFAP and a panel of inflammatory mediators were measured using Simoa HD-1 digital ELISA or a Luminex 200 instrument.Results: MFAP4 levels were elevated in patients with NPSLE compared to patients with non-NPSLE (p=0.031), more prominent in NPSLE patients with CNS involvement (p = 0.017). NfL and GFAP were higher in the total SLE cohort (p<0.001, p<0.001, respectively) as well as NPSLE subgroup (p<0.001, p<0.001, respectively), and in the subgroup of NPSLE patients with CNS involvement (p<0.001, p<0.001), compared to HC. NfL and GFAP levels correlated positively with MFAP4 in the NPSLE as well as the non-NPSLE subgroup (rho = 0.44 p=0.003, rho = 0.25 p = 0.004). VEGF was reduced in NPSLE patients compared to HC (p=0.015). MMP-9 was elevated in NPSLE compared to non-NPSLE (p=0.048). Inflammatory markers including IFN-α, IL-6, IL-10 and TNF-α, were elevated in the NPSLE group compared to HC (p<0.001, p=0.0026, p=0.042, p=0.007, respectively). In NPSLE patients the levels of MFAP4 correlated with TNF-α ( p=0.016) and IL-17 (p=0.0044) and with markers of blood brain barrier (BBB) disruption MMP-7 (p=0.005) and VEGF (p<0.001). In NPSLE patients with CNS manifestations MMP-3 and VEGF correlated with MFAP4 (p=0.011, p=0.0004, respectively).Levels of MFAP4 correlated with NfL, GFAP and proinflammatory cytokines and in NPSLE additionally with markers of BBB disruption, suggesting that MFAP4 is a marker of inflammation and vascular re-organization. Correlation of NfL and GFAP with MFAP4 may reflect CNS tissue damage.